Adolescents ’ Communication Problems in School - Porozovs, Juris; Aumeistere, Līga; Voita, Daina; Vaļēviča, Evita; Kauliņa, Anda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Violence among children and young people is a serious public health problem. Students attending schools with higher levels of bullying may show poorer school performance. The questionnaire of students and teachers from 3 Valmiera region schools was carried out. The results of questionnaire showed that students and teachers consider violence of adolescents as a serious problem. The majority of students often come to situations where their classmates are tampered. Many students and teachers consider that video security cameras must be installed in schools. Teachers think that more severe penalties must be applied for the perpetrator in the case of tampering the classmate. Students as well as teachers consider that interfacing problems of adolescents play a great role in teaching process.